(untitled) (Bodhi Path, 2024)
Mahapandit Rahul Sankrityayan was a man of multifaceted personality and a great scholar of Buddhism. He risked his life for the propagation and spread of Buddhism and traveled through difficult terrains. The extraordinary work Rahul Ji did in rediscovering and bringing to light the then extinct Buddhism in India and its related rare and magnificent texts is unparalleled and unforgettable. The revival of Buddhism, which had disappeared centuries ago, by the will of the people is a unique event in history. Buddhism was ousted from its birthplace. A crucial link in the historical development of Indian history had been severed. In the nineteenth and twentieth centuries, some enthusiastic youths paid attention to it, and once again, the land of India began to enrich its life with Buddhist philosophy and teachings. The first attempt to revive Buddhism in India was made by a Buddhist monk from Sri Lanka, Anagarika Dharmapala. Subsequently, three guru brothers - Bhadant Anand Kausalyayan, Rahul Sankrityayan, and Bhikshu Jagdish Kashyap played a significant role in the development of Buddhism. Tripitakacharya Rahul Sankrityayan dedicated the golden period of his life to the development of Buddhist literature, philosophy, culture, and religion. He had deep devotion towards Buddhism. This research paper is a modest attempt to shed light on his contributions to the development of Buddhism.